Enhancing Tajwid Skills through Harakah-Based Learning Media: An Evaluation of MPQu-Berkah among Schoolchildren - Nurliadin, Nurliadin; Chirzin, Muhammad; Arif, Mahmud; Khairudin, M (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga, Yogyakarta, 2024)
The research explores the efficacy of MPQu-Berkah, a harakah-based digital media, in enhancing tajwid skills among schoolchildren (Elementary Students), specifically focusing on Makhārijul hurūf and Ṣifātul hurūf. Utilizing a Nonequivalent Pretest-posttest Control Group Design, the study compares the tajwid proficiency of students engaging with MPQu-Berkah to those following traditional learning methods. The methodology encompasses pretests and posttests, alongside an independent t-test for statistical analysis, to evaluate the impact of the learning media on Quranic reading accuracy and fluency. Findings reveal a significant improvement in the experimental group's tajwid abilities, highlighted by an 11% average competency increase, evidencing MPQu-Berkah's effectiveness. The developed media, tailored for elementary education in the digital era, features audio-visual content designed to facilitate accessible and engaging tajwid learning. Despite the positive outcomes, the study acknowledges limitations due to its experimental setting and suggests future research to investigate the wider application and sustained impact of digital learning tools in religious education. This research underlines the potential for integrating multimedia tools in educational curricula, proposing a shift towards technology-enhanced learning environments to cater to the digital-native generation's needs. The findings advocate for a paradigm change in Quranic education, indicating that technological integration can substantially improve learning outcomes, contributing to the fields of educational technology and linguistic skill teaching.